Synthesis of Activated Carbon Honeycomb Monoliths under Different Conditions for the Adsorption of Methane - Liliana Giraldo; J.C. Moreno-Piraján (Adsorption Science & Technology)
Methane adsorption onto different types of carbon monoliths was studied at two temperatures (298.15 K and 303.15 K) and at pressures up to 35 atm in a volumetric adsorption apparatus. The mass basis results for methane adsorption indicated that the methane adsorption capacities of the carbon monoliths increased with increasing surface area, total pore volume and micropore volume. The maximum volumetric methane uptake of the carbon monoliths synthesized was 165 v/v at 298.15 K and 35 atm employing steam-activated monoliths derived from petroleum coal tar. The Clapeyron–Clausius equation was used to describe the interaction between the guest molecules and the adsorbent at low surface coverage and the energetic heterogeneous surface nature of the adsorbent, respectively. The methane storage capacity was found to be a function of the micropore volume and the developed superficial area.